Acute lumbosacral polyradiculopathy due to cytomegalovirus in advanced HIV disease: CSF findings in 17 patients. Issue 5 (November 1996) - Miller, R F; Fox, J D; Thomas, P; Waite, J C; Sharvell, Y; Gazzard, B G; Harrison, M J; Brink, N S
Abstract : OBJECTIVES: To describe the abnormalities in CSF from HIV infected patients with acute lumbosacral polyradiculopathy (ALP) caused by cytomegalovirus (CMV) infection. METHODS: Retrospective case notes and laboratory records were reviewed for 17 consecutive patients with CMV associated ALP admitted to specialist HIV/AIDS units at UCL Hospitals and Chelsea and Westminster Hospital. RESULTS: Infection with CMV was confirmed by detection of CMV DNA by polymerase chain reaction amplification in 15 patients (all of whom were negative by culture), by culture in one patient, and by objective clinical response to anti-CMV treatment in one patient. Only nine patients had a CSF pleocytosis 28-1142 (median 150) cells/mm3; in seven there was a polymorphonuclear (PMN) leucocyte preponderance. Protein concentrations in CSF were moderately or considerably raised in 13 patients; CSF: plasma glucose ratios were < or = 50% in five patients. Two patients had no pleocytosis, normal CSF: plasma glucose, and normal or near normal protein values. CONCLUSIONS: Abnormalities in CSF in CMV associated ALP are varied: only 50% of patients have a "typical" PMN preponderant pleocytosis. The diagnosis of this condition should not rely on demonstration of a PMN preponderant pleocytosis, but on identification of CMV DNA in CSF and the exclusion of other opportunistic infections and lymphoma in order that specific anti-CMV treatment may be instituted.